Re-evaluation of the mechanism of cytotoxicity of dialkylated lariat ether compounds. Issue 66 (5th November 2020) - Carrasquel-Ursulaez, Willy; Reeves, Ryan D.; Dehghany, Mahzad; Jones, Corey; Schomaker, Jennifer M.; Chanda, Baron
Abstract : The cytotoxicity of dialkylated lariat ethers has been previously attributed to their ionophoric properties. Abstract : The cytotoxicity of dialkylated lariat ethers has been previously attributed to their ionophoric properties. Herein, we provide evidence that these effects are due to loss of membrane integrity rather than ion transport, a finding with important implications for the future design of synthetic ionophores.